Anxiety Levels Associated With Noise In The Dental Clinic Among Children OF Age Group 6-15 Years - Joel Simon, Christopher; R, Mahesh; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Dental fear usually refers to a normal unpleasant emotional reaction to specific threatening stimuli occurring in situations associated with dental treatment, while dental anxiety is an excessive and unreasonable negative emotional state experienced by dental patients. These psychological states consist of apprehension that something dreadful is going to happen in relation to dental treatment. Dental fear and dental anxiety are often used indistinctly in the scientific literature, but they represent different progressive degrees of the same psychological condition. The terms dental fear and anxiety (DFA) will be used throughout this review when we refer to strong negative emotions associated with dental treatment among children. Dental treatment can be perceived as a painful and agonic experience, it can exert influence in the behavior of human beings, especially in children. This could be due to factors such as anxiety, and fear, which, together with anguish generated during dental treatment, can turn a rapid and successful visit into negative experience. Fear or anxiety due to noise produced in the dental clinic is rated third among reasons to avoid dental visits. Dental anxiety is a significant problem for patients and dental care providers. Quite a large number of studies have been conducted to identify the potential anxiety provoking stimuli present in the dental setting. These stimuli include the sight of the needle, smell of different dental materials, noise produced in dental clinic and various aspects of the drill such as its appearance, sound and feeling. The present study is aimed at one such factor that is noise in the dental clinic and its effect on patient’s anxiety.